Red giant pulsations from the suspected symbiotic star StHA 169 detected in Kepler data - Gavin Ramsay; Pasi Hakala; Steve B. Howell (Oxford Journals, 2022)
We present Kepler and Swift observations of StHa 169 which is currently classified as a symbiotic binary. The Kepler light curve shows quasi-periodic behaviour with a mean period of 34 d and an amplitude of a few per cent. Using Swift data, we find a relatively strong UV source at the position of StHa 169 but no X-ray counterpart. Using a simple two-component blackbody fit to model the combined Swift and 2MASS spectral energy distribution and an assessment of the previously published optical spectrum, we find that the source has a hot (˜10 000 K) component and a cooler (˜3700 K) component. The Kepler light is dominated by the cool component and we attribute the variability to pulsations in a red giant star. If we remove this approximate month long modulation from the light curve, we find no evidence for additional variability in the light curve. The hotter source is assigned to a late B or early A main-sequence star. We briefly discuss the implications of these findings and conclude that StHA 169 is a red giant plus main-sequence binary.